1991
DOI: 10.1007/bf01955530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of high intensity green light phototherapy in the treatment of neonatal jaundice

Abstract: Two matched groups of term newborn infants with idiopathic jaundice were subjected to intensive double direction green or blue light phototherapy (PT). The efficacy of treatment was expressed as rate of decline of serum bilirubin concentration after 6, 12 and 24 h of light exposure. More rapid response was obtained using conventional blue lamps (Philips TL/20W/52) than green lamps (Sylvania F20T12/G). Whole duration of PT was significantly shorter using blue lamps (P less than 0.05). However, less postphotothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
8
1
4
Order By: Relevance
“…12 In the present study, we took advantage of the narrow spectrum of the LEDs in order to reassess the controversial efficacy of green versus blue phototherapy. [4][5][6][7][8][9][10] Notwithstanding theoretical reasoning for better penetration of green and better absorption of blue light, we found no statistically significant difference in the efficacy of blue-green light over either blue or white light.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…12 In the present study, we took advantage of the narrow spectrum of the LEDs in order to reassess the controversial efficacy of green versus blue phototherapy. [4][5][6][7][8][9][10] Notwithstanding theoretical reasoning for better penetration of green and better absorption of blue light, we found no statistically significant difference in the efficacy of blue-green light over either blue or white light.…”
Section: Discussioncontrasting
confidence: 60%
“…[4][5][6][7][8][9][10] Data obtained in in vitro investigations 13 and in Gunn rat experiments 14 suggested that green fluorescent light has a low efficiency in lowering bilirubin concentrations. However, clinical studies on the effect of green fluorescent light on the rate of bilirubin photodegradation showed it to be of superior, 5 similar 6,8 or inferior 7 efficiency when compared with blue fluorescent light.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations